The Effect of Skepticism, Independence, Professionalism, and Competence towards Audit Quality (in Covid-19 situation) - Maria Lintang Dwilitani Istiadi; David Ashedica Adechandra Pesudo (Politeknik Negeri Madiun, 2021)
This study aims to determine the effect of auditor's skepticism, independence, professionalism, and competence towards audit quality, especially in Covid-19 situation. The sample of this study are the auditors who work in CPAs firm in Semarang and Solo. The data analysis technique used in this study is Multiple Regression and processed using SPSS. This study indicates that skepticism and competence does not influence audit quality while independence and professionalism influence audit quality.